THE ROLE OF PARENTS IN SHAPING POLITICAL AWARENESS IN FIRST-TIME VOTERS AMONG FAMILIES IN THE SOUTH SANGATTA DISTRICT EAST KUTAI REGENCY - Rahmat, Ismail (Islamic Family Law, STAI Sangatta Kutai Timur, 2023)
The family is considered the primary pillar in children's lives journey. Within the family's scope, there are many lessons and teachings that can be acquired, including in the realm of education. Education takes on various manifestations that serve as the foundation for children's development and preparation for life outside the family. One aspect of education that was often overlooked is political education. Political education is crucial for shaping children into quality citizens. Therefore, the family plays a vital role in delivering political education to children. Parents, as family members, have a primary role in the delivery of the political education. This research is descriptive-quantitative in nature and employs proportional stratified random sampling techniques. Data was obtained through interviews and the use of questionnaires. The research findings indicate that the parental education level, whether elementary, junior high, high school, or a bachelor's degree, influences their role in providing political education to children. Parents with higher levels of education tend to play a more significant role in delivering political education. Efforts to enhance the political awareness of children include providing the comprehension, political knowledge, discussions about politics, and supporting children's participation in political activities. However, in the process, parnts face several obstacles their efforts to instill political awareness in children as first-time voters in the South Sangatta Selatan District, East Kutai. These obstacles involve factors such as the parents' education level, children's attitudes, socio-economic situations, and socio-cultural aspects in the children's social circles. These factors present challenges in the endeavor to instill political awareness in children.